Usability Evaluation of the Student Centered e-Learning Environment - Junus, Inas Sofiyah; Santoso, Harry Budi; Isal, R. Yugo K.; Utomo, Andika Yudha (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Student Centered e-Learning Environment (SCeLE) has substantial roles to support learning activities at Faculty of Computer Science, Universitas Indonesia (Fasilkom UI). Although it has been used for about 10 years, the usability aspect of SCeLE as an e-Learning system has not been evaluated. Therefore, the usability aspects of SCeLE Fasilkom UI as a learning support system and what makes SCeLE Fasilkom UI an ideal system are not known yet. Motivated by the mentioned conditions, the researchers found an urge to conduct a usability evaluation in order to propose a set of recommendation for SCeLE usability improvement, based on usability evaluation reflecting both students and lecturers experience as user. In this present research, the usability testing was conducted for SCeLE, targeting learning activities underwent by undergraduate students at Fasilkom UI, in the form of blended mode online learning. The data collection stage in the usability testing was performed by distributing questionnaire to students and interviewing several lecturers and students. The collected data was then analyzed and interpreted to obtain usability problems and solution alternatives. The quantitative data was analyzed using central tendency as reference, while the qualitative data was analyzed using theme-based content analysis. Data interpretation was performed by determining how to handle each kind of data based on the theme, and classifying each of the identified usability problem based on its severity rating. The recommendations constructed to solve the usability problems were based on solution alternatives from the analyzed data supported by literature study. The present research comes up with seven main recommendations and an extra recommendation. The main recommendations are solutions to tackle the identified usability problems, while the extra recommendation is not directly related to any of identified usability problems, but was considered potential to improve the SCeLE usability.